A Comparison of Survival and Secondary Contraction in Expanded Versus Conventional Full-Thickness Skin Grafts: An Experimental Study in Rats - Kamran, As'adi (Open Science Company, LLC, 2012)
Aim: The aim of this experimental study is based on a comparison between the effect of expanded versus nonexpanded full-thickness skin grafts (FTSGs) on survival and secondary wound contraction. Methods: A total of 20 quadrangular-shaped, full-thickness skin defects with dimensions of 2 × 3 cm were created on the backs of 10 rats. Two groups were specified in this study depending on the coverage of the aforementioned defect areas using expanded versus conventional full-thickness grafts (n = 10 per group). The survival area of each graft and the amount of graft/wound contraction (secondary contraction) were measured by computerized planimetry on days 0, 7, 30, and 90. Results: The mean graft areas achieved were 5.8 ± 0.6, 4.2 ± 1.5, and 1.2 ± 1.1 cm(2) (P < .001) in the expanded FTSGs group and 5.3 ± 0.9, 3.3 ± 1.3, and 0.98 ± 0.8 cm(2) (P < .001) in the nonexpanded FTSGs group on days 7, 30, and 90, respectively. Graft area reductions (secondary contraction) were 1.7 ± 0.9 and 2.1 ± 1.2 cm(2) (P = .8) on day 30 and 2.1 ± 1.3 and 2.86 ± 0.8 cm(2) (P = .3) on day 90 in the expanded and nonexpanded groups, respectively. Conclusion: According to this study, FTSGs that were harvested from tissue expansion revealed biological behaviors that were comparable with those of conventional grafts.